2019
DOI: 10.1002/hbm.24679
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal imaging reveals a complex pattern of dysfunction in corticolimbic pathways in major depressive disorder

Abstract: Major depressive disorder (MDD) is highly prevalent and associated with considerable morbidity, yet its pathophysiology remains only partially understood. While numerous studies have investigated the neurobiological correlates of MDD, most have used only a single neuroimaging modality. In particular, diffusion tensor imaging (DTI) studies have failed to yield uniform results. In this context, examining key tracts and using information from multiple neuroimaging modalities may better characterize potential abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…All participants provided written informed consent after oral explanation of study procedures, which were approved by the NIH Combined Central Nervous System Institutional Review Board. Independent analyses and results from these studies have previously been published [6,[21][22][23][24].…”
Section: Participants and Study Designmentioning
confidence: 99%
“…All participants provided written informed consent after oral explanation of study procedures, which were approved by the NIH Combined Central Nervous System Institutional Review Board. Independent analyses and results from these studies have previously been published [6,[21][22][23][24].…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Whereas structural MRI is used to examine macroscopic structural properties of the brain (e.g., volume or cortical thickness), diffusion MRI (dMRI) is able to better characterize properties of tissue microstructure, most notably white matter (WM) microstructure 13 . Previous research has demonstrated that WM structure can be an important factor associated with clinical response to typical antidepressant medications 14,15 , yet only two studies to date have used dMRI to investigate the role of WM in patient response to ketamine treatment 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…A study employed DTI, magnetic resonance spectroscopy (MRS), rs-fMRI, and magnetoencephalography (MEG) and revealed patterns of abnormalities of patients with major depressive disorders. These patterns included factors in the neurotransmitters (glutamate concentration), white matter fibers (fractional anisotropy), and functional excitations (fMRI) [157] . A multimodal MRI study involves structural MRI and ASL to assess grey matter volume and regional cerebral blood flow in MDD patients.…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 99%